A Tale of Two Moralities. Issue 2 (September 2018) - Zahid, Adnan; Lone, Razi Allah
This case describes an ethical problem faced by the owners of a reasonably successful business. It gives students an opportunity to analyze the contrasting approaches of the two owners of this business towards an ethical dilemma commonly faced by those businesses in Pakistan that have to pay heavy duties on imported goods. The case highlights the fact that morally upright individuals can be pushed into very difficult situations wherein they, despite their good intentions, at times choose not to uphold duties imposed by law and morality. The difficulty felt in remaining within the confines of law, and upholding moral principles is amplified by the cumulative effects of moral failures that become endemic to a society. The pressure created by the policies of a government deemed corrupt, inefficient and, in the final analysis, illegitimate on the one hand, and unscrupulous competitors on the other, can become, at times, important contributors to morally questionable behaviour. This brings to the fore the dilemma of an individual trying to make an honest living in a very unfavourable context. The moral conundrum may be resolved either by making the difficult choice of following the law to the hilt, or through constructing an argument that legitimizes an illegal and seemingly unethical course of action.